Impact of SQ4R on reading comprehension of university students in an English for specific purposes (ESP) Course - Bangkhadara, Wachiraya; Wilang, Jeffrey; Newprasit, Nillawan (Politeknik Negeri Bali, 2024)
This study aimed to achieve three objectives: to identify the active reading strategies employed by undergraduate students in an English for Specific Purposes (ESP) course, to evaluate the effectiveness of the SQ4R model in enhancing students' reading comprehension, and to know their insights about the model. Descriptive analysis of survey data revealed significant positive changes in study strategies following the SQ4R intervention. Students demonstrated notable improvement in organizing material using flow charts, indicating enhanced capability in managing complex information. Similarly, highlighting techniques became more strategic, focusing on critical information. The organization of annotations into various formats also improved, pointing to more advanced note-taking and data processing skills. Additionally, the creation of practice tests increased, signifying greater engagement in active recall and testing. These findings underscore a significant shift toward more effective and engaged learning strategies among students. T-test results revealed a significant improvement in pre-test and post-test scores, confirming the effectiveness of the SQ4R model. Students' positive feedback further supports the utility of this model in enhancing active reading practices. The implications of this study suggest that the SQ4R model can be an effective tool in improving reading comprehension and engagement in ESP courses, with potential applications in other educational contexts as well.